Analisis Pemberdayaan Masyarakat Di Bidang Kesehatan Masyarakat Desa Sirnabaya Kecamatan Rajadesa Jawa Barat - Endrian Mulyady Justitia Waluyo; Jajuk Kusumawaty; Elis Noviati; Lilis Lismayanti; Adi Nurapandi (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: The results of the study in Sirnabaya Village have problems with stunting and non-communicable diseases (Hypertension and Diabetes Mellitus) and waste management. Based on the results of the ranking of community problems, there are problems regarding readiness to improve health management: knowledge of mothers who have toddlers, Ineffective health management: adolescent reproductive health, readiness to increase community coping: increased knowledge of tasks in family development stages in the community, readiness to improve community health management of couples of childbearing age. Objective: The purpose of this service was community empowerment in Sirnabaya aims to improve health status. Method: community empowertment used is the method of counseling or lectures and demonstrations or practice. Result: The results are to train children's motor skills, and increase knowledge about adolescent health, couples of childbearing age, families, and the elderly. The results of knowledge on the average increase, especially in the elderly. Conclusion empowering the Sirnabaya community is to increase the knowledge and skills of cadres in solving health problems to improve the health of the community.